PENGARUH PERBEDAAN KARAKTERISTIK MULTIMEDIA TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA KONSEP SISTEM PERTAHANAN TUBUH - Pratiwi, Dasrieny (UNIVERSITAS MUHAMMADIYAH METRO, 2012)
The aim of this study to improve student critical thinking in immune system lesson using the different characteristic of multimedia. There are four characteristics of multimedia to compare in this study such as text (long text an short text), narration (yes or no), sound effect (yes or no), sparkle in animation of multimedia (yes or no). This study is using the static group pretest-posttest design. Which compare two type of multimedia that have a different characteristic to improve student critical thinking. This study is to involved 66 student of science high school attending 11th grade. They were devided two class; experimen-1 (n=31) and experimen-2 (n=3). Data was collected from pretest and posttest on immune system lesson. The result of this study shown that multimedia type 1 could improved student critical thingking on immune system lesson Kata kunci: Karakteristisk multimedia, berpikir kritis, sistem pertahanan tubuh